A new genus and species of felt scale (Hemiptera: Coccoidea: Eriococcidae) from New Caledonia - Hodgson, Chris; Mille, Christian; Cazères, Sylvie (Zootaxa, 2014)
A new genus of Eriococcidae, Choneochiton Hodgson, is introduced to take a new species, Choneochiton casuarinae Hodgson, Mille & Cazères, off Casuarina collina (Casuarinaceae) from New Caledonia. All stages except the pupa and prepupa are described and illustrated. The new species is thought to be endemic to New Caledonia.